Kesalahan Penerjemahan Bahasa Indonesia-Bahasa Arab (Studi Kasus Hasil Terjemahan Mahasiswa Prodi Pendidikan Bahasa Arab IAIDA Blokagung Banyuwangi) - Mahbub; M. Alaika Nasrullah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
The aim of this study is to identify and describe the errors in the translation of the Indonesian language into Arabic and the causes that occurred in the results of the translations of Indonesians-Arabic texts by students of the Arabic Language Education Institute of Islamic Religion Darussalam Blokagung Banyuwangi. This type of research is qualitative research. This research data is obtained from the translations of the students taken using analytical techniques. After the translation results are obtained, then the error identification, error classification and error reconstruction is carried out. The results of this research are, the forms of errors that occur in the students' translations are word selection errors, word deletion errors, word addition errors and word form errors. As for the cause of the error, there are two factors underlying the occurrence of the errors found, interlingual transfer and intralingual transfer.